Caspase recruitment domain-containing protein 9 (CARD9) knockout reduces regional ischemia/reperfusion injury through an attenuated inflammatory response. - Xing Qin; Matthew R Peterson; Samantha E Haller; Li Cao; D Paul Thomas; Guanglong He (PLoS ONE)
Ischemic heart disease remains a leading cause of morbidity and mortality in the United States. Interventional reperfusion induces further damage to the ischemic myocardium through neutrophil infiltration and acute inflammation. As caspase recruitment domain-containing protein 9 (CARD9) plays a critical role in innate immune response and inflammation, we hypothesized that CARD9 knockout would provide protection against ischemia and reperfusion (I/R) injury through attenuation of acute inflammatory responses. C57BL/6 wild-type (WT) and CARD9-/- mice were subjected to 45 min left anterior descending (LAD) coronary artery occlusion followed by 24-h reperfusion. Area at risk (AAR) and infarct size were measured by Evans blue and triphenyltetrazolium chloride (TTC) staining. Frozen heart sections were stained with anti-mouse GR-1 antibody to detect infiltrated neutrophils. Concentrations of cytokines/chemokines TNF-α, IL-6, CXCL-1 and MCP-1 were determined in heart tissue homogenate and serum by ELISA assay. Western immunoblotting analyses were performed to measure the phosphorylation of p38 MAPK. Our results indicate that following I/R, infarct size was significantly smaller in CARD9-/- mice compared to WT. The number of infiltrated neutrophils was significantly lower in CARD9-/- mice compared to WT. Levels of TNF-α, IL-6, CXCL-1 and MCP-1 were significantly reduced in heart tissue and serum from CARD9-/- mice compared to WT. CARD9-/- mice also exhibited significantly lower levels of phosphorylated p38 MAPK. Taken together, our results suggest that CARD9 knockout protects the heart from ischemia/reperfusion (I/R) injury, possibly through reduction of neutrophil infiltration and attenuation of CARD9-associated acute inflammatory signaling.